Chemical Characterization and Categorization of Fly Ash Waste from PT Indonesia Power II Cilacap: An XRF Analysis: Karakterisasi Kimia dan Kategorisasi Abu Terbang dari PT Indonesia Power II Cilacap: Analisis XRF - Fauzi, M. Abd Rahman (Universitas Muhammadiyah Sidoarjo, 2023)
This study presents the chemical characterization and categorization of fly ash waste obtained from the combustion of coal by PT Indonesia Power II Cilacap. The fly ash samples were sieved using multilevel sieve shakers with sizes of 120, 270, and 325 mesh to achieve uniform particle sizes. Chemical and oxide element analysis was conducted using X-Ray Fluorescence (XRF) on 100-gram portions of each sample at the Integrated Research and Testing Laboratory (LPPT) UGM. The results reveal that the fly ash from PT Indonesia Power II Cilacap belongs to class C due to its CaO content exceeding 10% (mass %). The findings contribute to the understanding of fly ash waste characteristics and its potential for further research as an adsorbent. Highlights: Chemical Characterization of Fly Ash: Analysis using X-Ray Fluorescence (XRF) revealed the composition of fly ash waste obtained from PT Indonesia Power II Cilacap, with a significant CaO content of 13.70% (mass %). Categorization into Class C: The high CaO content (>10%) classifies the fly ash as Class C, based on ACI Manual of Concrete Practice guidelines, indicating its suitability for specific applications in further research. Potential as an Adsorbent: The findings contribute valuable insights into the utilization of fly ash waste as an adsorbent material, suggesting potential applications in environmental remediation and engineering studies.